The Questions of Jesus and Mazu Human or Beyond? - Dickman, Nathan Eric (2016)
Religions answer existential questions. Yet questions recur in the direct discourse of central characters in religious literature. The Gospels depict Jesus asking hundreds of questions. The classical Chan master, Mazu, is depicted in the Mazu Yulu asking just as many questions. Despite attention given to nearly every aspect of religion, there is a lacuna in scholarship about questions posed by religious characters. This is puzzling because philosophical hermeneutics and other post-Heideggerian philosophies emphasise the priority of questioning. Questioning, for Heidegger, defines the human condition. Can these figures ask genuine questions? The task of the present article is to speculate about whether any of Jesus' or Mazu's questions are open-ended ones aimed at understanding what another says. I take up this task with a hermeneutic roughly aligned with Paul Ricoeur.